Poly(4-vinylpyridine)iodonium triiodide: A new efficient catalyst for the synthesis of 3,3-diheteroaromatic oxindole analogues - JOHARI, SUZAIMI; KHALIGH, NADER GHAFFARI (Malaysian Catalysis-An International Journal, 2023)
The synthesis of a series of 3,3-diheteroaromatic oxindoles has been effectively produced through treatment of indole-2,3-dione (isatin) with various indoles and pyrroles using quaternized poly(4-vinylpyridine)iodinium iodide , under solvent-free condition and neutral medium. The reaction proceeds rapidly with excellent yields. This catalyst has been shown to be stable and highly recyclable.